Investigating Japanese Vocabulary Learning Strategies of Indonesian Vocational Business Students - Eny Widiyowati; Titien Indrianti; Esther Hesline Palandi; Cahyo Ramadhan Pratama (Merwin Publisher, 2026)
Mastering Japanese vocabulary is a critical yet challenging component for vocational students aiming for professional proficiency in business contexts. This study investigates the specific language learning strategies (LLS) utilized by vocational higher education students to acquire Japanese lexis. Using Oxford’s Strategy Inventory for Language Learning (SILL) framework, data were collected from 71 sixth-semester Business Administration students and analyzed using descriptive statistics. The results reveal a dominant preference for affective (85%) and social strategies (81%), indicating that learners rely heavily on emotional regulation and peer interaction, whereas metacognitive (63%) and memory strategies (60%) were the least employed. These findings highlight a diverse learning approach as signified by the high employment of socio-affective strategy, but a critical deficiency in self-regulated learning and systematic retention. Consequently, the study implies that vocational curricula must integrate explicit strategy instruction to help students transition from social dependence to greater learner autonomy and achieve more effective vocabulary mastery.